Microstate analyses as an indicator of anesthesia-induced unconsciousness. (March 2023) - Lapointe, Andrew P.; Li, Duan; Hudetz, Anthony G.; Vlisides, Phillip E.
Highlights: Differences in EEG microstates were observed between three phases of perioperative care (pre-induction, surgery and post-anesthesia care unit). We observed a topographical map known as microstate F during surgery, which has been previously shown during propofol infusion. Age effects were observed on the mean duration and mean occurrence of microstates, particularly during recovery. Abstract: Objective: The objective of this study was to identify differences in electroencephalographic microstate topographies across three perioperative phases: anesthetic pre-induction, surgical anesthesia, and post-anesthesia care unit (PACU) admission. Methods: Whole-scalp 16-channel electroencephalographic recordings were taken throughout the perioperative period on n  = 22 adult, non-cardiac surgical patients. Results: Several differences between perioperative periods were identified. Most notably, during surgical anesthesia, patients demonstrated increased mean duration and, consequently, a reduction in the occurrence of microstates when compared to both preoperative baseline and PACU admission. We also observed the presence of microstate F with propofol anesthesia during surgery, which had been previously identified with propofol infusion in laboratory settings using human volunteers. Finally, we observed inverse age effects with mean occurrence and duration of microstates, particularly during PACU recovery. Conclusions: Microstate duration is significantly increased during surgery compared to both pre-induction and PACU recovery. These data suggest that microstate topographies may be useful in monitoring anesthetic depth. Significance: This work highlights the potential for microstate analysis in the perioperative setting. We identified distinct topographical signatures across perioperative periods and with increasing age, which is predictive of post-operative delirium.